2004
DOI: 10.1007/s00464-004-8809-x
|View full text |Cite
|
Sign up to set email alerts
|

The laparoscopic repair of suprapubic ventral hernias

Abstract: Although technically demanding and time-consuming, the LRSPH is safe and technically feasible. Moreover, it results in a low recurrence rate and is applicable to large or multiply recurrent hernias. Transabdominal suture fixation to the bony and ligamentous structures produces a more durable hernia repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(12 citation statements)
references
References 17 publications
(16 reference statements)
1
9
0
2
Order By: Relevance
“…First, single-incision laparoscopic preperitoneal mesh repair minimized recurrence of supra-umbilical incisional hernia. According to the previous reports, the recurrence rate of laparoscopic repair for supra-umbilical hernia was around 6% [ [9] , [10] , [11] ]. Repair of a supra-umbilical hernia is still a surgical challenge because of the highest pressure at the lower abdominal wall in the erect position.…”
Section: Discussionmentioning
confidence: 99%
“…First, single-incision laparoscopic preperitoneal mesh repair minimized recurrence of supra-umbilical incisional hernia. According to the previous reports, the recurrence rate of laparoscopic repair for supra-umbilical hernia was around 6% [ [9] , [10] , [11] ]. Repair of a supra-umbilical hernia is still a surgical challenge because of the highest pressure at the lower abdominal wall in the erect position.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrences may also be related to awkward hernia localizations, particularly with larger defects in the Tx/IS group extending toward the iliac crest or ribs/sternum [180,181]. The single conversion in the Tx/Is group and one of the three recurrences were caused by a potentially insufficient mesh overlap between the kidney graft and the iliac crest.…”
Section: Complicationsmentioning
confidence: 99%
“…The double-crown technique is our choice of treatment in incisional hernias; if necessary, we use transabdominal sutures to position a large mesh properly. Carbonell et al reported two cases of recurrence before applying multiple sutures directly to the pubis and Cooper’s ligament [ 11 ]. Contrary to recommendations in the literature, we did not apply transabdominal sutures to fix the inferior border of the mesh and recurrence was not observed during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%